Research on Piston Avoidance Valve Pit Milling Method - Zhao, Changlong; Ma, Hongnan; Zhao, Qinxiang; Jia, Xiaoyu; Zhang, Haifeng (Manufacturing Technology Journal, 2024)
In order to improve the processing efficiency and surface quality of the piston avoidance pit, reduce labor costs, and make the processing of the piston avoidance pit meet the modern production re-quirements, it is realistic and feasible to combine Pro/E and Mastercam software to complete the processing of the piston avoidance pit. Two different kinds of piston pits are selected for machining, and the 3D model of the piston pits is established by Pro/E software, and the process preparation and parameter setting are realized by Mastercam software, and the NC machining simulation is con-verted into NC code to realize the machining of the piston pits; two different surface finishing meth-ods are used in Mastercam software to complete the machining of the piston pits. The two different surface finishing methods are analyzed for their effects on the programming of the piston avoidance pit, and a method to improve the efficiency and surface quality of the piston avoidance pit is derived to further improve the machining method of the piston avoidance pit and provide reference for the subsequent machining of the piston avoidance pit.
Keywords: Piston avoidance valve pit; CNC machining; Surface finishing; Mastercam